MANFAAT PENGUATAN OTOT TRANSVERSUS ABDOMINIS DAN MUSCLE PUMPING EKSTREMITAS INFERIOR TERHADAP DIASTASIS RECTI ABDOMINIS PADA IBU NIFAS - Nurmawati, Eka; Dentawyanjani, Fitriani; Maryam, Hanna; Mutiara, Etika Khayyu; Fitrihadi, Enny (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
postpartum or puerperal period is a time to recover from childbirth finished up the tools again as pre- pregnant uterus . This long period is 6-8 weeks postpartum. Bobak ( 2000:119 ) explains that during pregnancy the abdominal wall muscles stretch and end up losing a little muscle tone . To determine the benefit transversus abdominis muscle strengthening and muscle pumping inferior extremity of the diastasis recti abdominis in new mothers in hospitals Cilacap . The research used in this study is a quantitative analysis of the draft Quasi experiment with a sample of 60 postpartum women with postpartum mothers criteria that have diastasis recti â‰¥ 0.5 cm . The average maternal postpartum diastasis recti before action is 1.9333 cm with a standard deviation of 0.25155 . While diastasis recti postpartum mothers after the act is 1.7833 cm with a standard deviation of 0.41545 . P value : 0.000 , so it can be concluded that the alpha 5% of the results obtained are the benefits of strengthening muscles and the transversus abdominis muscle of the lower extremities pumping diastasis recti abdominis in new mothers in hospitals Cilacap . Keywords : diastasis recti , strengthening the transversus abdominis muscle , muscle pumping inferior extremity